2016
DOI: 10.3390/met6050116
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of MgZnCa Bulk Metallic Glass Composites with Ti-Particle Dispersion

Abstract: Rod samples of Mg 60 Zn 35 Ca 5 bulk metallic glass composites (BMGCs) dispersed with Ti particles have been successfully fabricated via injection casting. The glass forming ability (GFA) and the mechanical properties of these Mg-based BMGCs have been systematically investigated as a function of the volume fraction (V f ) of Ti particles. The results showed that the compressive ductility increased with V f . The mechanical performance of these BMGCs, with up to 5.4% compressive failure strain and 1187 MPa frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The samples were cut into rods with 10 mm length and 2 mm diameter, and polished at both ends to ensure surface flatness. Our previous studies have reported the microstructure, thermal properties, mechanical properties, and degradation behavior of Mg 60 Zn 35 Ca 5 BMGCs with 40 vol% Ti particles (with particle size of 75–105 μm) [4,5]. Mg 60 Zn 35 Ca 5 BMGCs with 40 vol% Ti particles possess the amorphous matrix and exhibit a compressive strength of around 800 MPa, and the calculated degradation rate around 0.26 mm/year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were cut into rods with 10 mm length and 2 mm diameter, and polished at both ends to ensure surface flatness. Our previous studies have reported the microstructure, thermal properties, mechanical properties, and degradation behavior of Mg 60 Zn 35 Ca 5 BMGCs with 40 vol% Ti particles (with particle size of 75–105 μm) [4,5]. Mg 60 Zn 35 Ca 5 BMGCs with 40 vol% Ti particles possess the amorphous matrix and exhibit a compressive strength of around 800 MPa, and the calculated degradation rate around 0.26 mm/year.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro degradation behavior of Mg 60 Zn 35 Ca 5 BMGC was evaluated well in our previous work [4]. The dispersion of titanium particles within the composite markedly improve the compressive strength and brittleness of Mg 60 Zn 35 Ca 5 BMGC relative to those of conventional biodegradable implants made of synthetic polymers, rendering it a suitable candidate for developing load-bearing bone fixation devices [5].…”
Section: Introductionmentioning
confidence: 96%
“…Most of the existing works have been carried out by selecting the composition that can form metallic glass with a large D c [26][27][28][29][30][31][32][33][34], while research on metallic glass with a small D c is still rarely reported. If a fourth component is added into the aforementioned compositions, the changes in the structure of amorphous matrix and mechanical properties of the alloys are worth noting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain softening induced by the formation of shear bands in the glassy matrix cannot be compensated by the strain hardening provided by these ductile phases during deformation. Overall, the microscopic strain-softening of BMG composites dominates their plastic deformation [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In this regard, shape memory B2 CuZr crystals were introduced into a glassy matrix as an alternative reinforcing phase because the B2 CuZr crystals usually show a pronounced work hardening during deformation due atmosphere, which were remelted at least for three times to achieve chemical homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a new class of composites, called bulk metallic glass (BMG) composites, have been explored by introducing ductile crystalline phases ex situ or in situ in a glassy matrix in order to enhance the ductility or/and toughness at the cost of the high strength of intrinsically brittle BMGs [4][5][6][7][8][9][10][11][12][13][14][15]. During deformation, ductile crystals in BMG composites may serve as heterogeneous nucleation sites for the initiation of shear bands and act as attraction or pinning centers during shear band propagation.…”
Section: Introductionmentioning
confidence: 99%